Immediate Vs Delayed Vitrectomy for The Management of Vitreous Hemorrhage Due to Proliferative Diabetic Retinopathy - Vina Karina Apriyani; Grimaldi Ihsan; Rova Virgana; Iwan Sovani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Surgical approach in vitreous hemorrhage (VH) secondary to diabetic retinopathy remains the procedure of choice for non-clearing VH. However, the most appropriate timing of vitrectomy is yet to be defined. With improvements in surgical techniques, it is reasonable to operate on such patients that have no spontaneous improvement. Objective: To compare the characteristics between groups of patients who underwent immediate and delayed vitrectomy for the management of vitreous hemorrhage due to proliferative diabetic retinopathy (PDR). Methods: Retrospective review of 35 patients who underwent vitrectomy for VH secondary to PDR. Patients were excluded if they had prior vitrectomy, follow up < 1 month post-operatively, other retinal pathology, VH secondary to other causes, uveitis, or advanced glaucoma. Primary outcome was visual acuity in patients receiving immediate (< 30 days) versus delayed (> 30 days) vitrectomy. Secondary analyses included post-surgical complications. Results: 35 eyes were included, 13 eyes had immediate vitrectomy while 22 eyes had delayed vitrectomy. There was no difference between the groups in terms of age, gender, diabetes control, or diabetes duration. Pre-operative and final visual acuities were evaluated, including 7 days, 30-days and 3-months in both Groups. Complications within 3 months were dominantly seen in the delayed vitrectomy Group. Conclusion: Immediate vitrectomy for VH due to PDR decreases time spent with vision loss, and decreases post-surgical complications. Modern vitrectomy surgery is safe and may be considered earlier in VH management.